Looked After Children as Decision Makers: Family Group Conferences in Practice. Issue 3 (2nd July 2020) - Edwards, Deanna; Parkinson, Kate; Fisher, Tim; Owen, James
ABSTRACT: Family Group Conferences (FGCs) are a family-led approach to social care decision making. The fundamental philosophy behind FGCs is that families are the experts on their own situations and as such should lead decision-making. The model advocates that children should be at the centre of decisions about them and should be supported to have their say at their FGC. The voice of looked after children too often gets lost in decision-making processes. Children report that professionals make decisions about them, rather than with them. FGCs have the potential to meaningfully engage with looked after children. Many services already offer FGCs to looked after children, either to consider family alternatives to local authority care, to make contact arrangements or to engage children in the care planning process. This paper will examine the use of FGCs in engaging with looked after children. It applies a case study approach, focusing on the Camden FGC Service, which has been offering FGCs to looked after children for several years. It will also draw on the existing evidence base that examines the use of FGCs with looked after children. In practice, sometimes the voice of the child can become overlooked at their FGC. Children report that their opinions get ignored by the adults in their family. Hence, this paper concludes with a discussion of how to ensure that looked after children are meaningfully engaged in decision making about their lives.